2021
DOI: 10.1186/s12974-021-02333-6
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of circular RNA CDC14A peripherally ameliorates brain injury in acute phase of ischemic stroke

Abstract: Background Inflammation is integral to the pathophysiology of ischemic stroke and a prime target for the development of new stroke therapies. The aim of the present study is to seek out the regulatory mechanism of circCDC14A in neuroinflammatory injury in tMCAO mice. Methods The expression level of circCDC14A in peri-infarct cortex and plasma of mice were detected by qPCR. The localization of circCDC14A in peripheral blood cells and peri-infarct co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…5,33 Recently, several studies found that circRNAs were involved in the pathogenesis of AIS by regulating immunoinflammatory reactions. 17,34,35 The circRNAmediated ceRNA mechanism can be used for the analysis of the molecular basis of various diseases. Hence, constructing a ceRNA network of immune-related circRNAs should help elucidate the inflammatory mechanisms in AIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,33 Recently, several studies found that circRNAs were involved in the pathogenesis of AIS by regulating immunoinflammatory reactions. 17,34,35 The circRNAmediated ceRNA mechanism can be used for the analysis of the molecular basis of various diseases. Hence, constructing a ceRNA network of immune-related circRNAs should help elucidate the inflammatory mechanisms in AIS.…”
Section: Discussionmentioning
confidence: 99%
“…16 Further study revealed that circCDC14A played a critical role in the regulation of inflammatory reactions during AIS. 17 However, the role of circRNAs serving as ceRNAs in the immune and inflammatory mechanisms of AIS remains less studied. In addition, there are no published studies on the expression of circRNAs in TIA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have demonstrated that circRNAs were involved in the pathogenesis of stroke‐related neuroinflammation 30–32 . In a mouse stroke model, knockdown of neutrophil‐derived circCDC14A inhibited astrocyte activation and alleviates neurological damage after cerebral ischemia 31 .…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs exert critical roles in various pathogenic processes, including ischemic stroke 17 . For example, circCDC14A was highly expressed in the mouse model of ischemic stroke and knockdown of circCDC14A attenuated brain damage during acute ischemic stroke 18 . CircRNA BBS2 (circBBS2, ID: hsa_circ_0039457), originated from the 2‐7 exons of the BBS2 gene, was reported to be down‐regulated in ischemic stroke patients 19 .…”
Section: Introductionmentioning
confidence: 99%